the answer is true i think
Answer:
it is true
Step-by-step explanation:
3x - 12 = 17
7(x + 1) = 14
1- 6x = -11
4x + 5 = 3
Answer: 1 - 6x = -11
Step-by-step explanation:
For each expression, substitute x for 2 to determine which is the correct expression:
3x - 12 = 17
3(2) - 12 = 17
6 - 12 = 17
-6 17
Because the number on the left side of the equation doesn't equal the number on the right, this first equation is incorrect.
7(x + 1) = 14
7(2 + 1) = 14
7(3) = 14
21 14
This second equation is incorrect as well.
1 - 6x = -11
1 - 6(2) = -11
1 - 12 = -11
-11 = -11
Because the number on the left equals the number on the right, the third equation is correct.
I hope this helps! :)
a = b − 2
What is the solution to the set of equations in the form (a, b)?
(−2, −2)
(−3, −1)
(−9, −7)
(−5, −3)
The solution to the set of equations in the form (a, b) is (-5, -3).
Hence, 4th option is the right choice.
A system of equations, also known as an equation system or a set of simultaneous equations, is a finite collection of equations for which common solutions are found.
We are given two equations in a and b and are asked to find the solution to them. The equations are:
a - 3b = 4 . . . . . . . . . . . . . . (1)
a = b - 2 . . . . . . . . . . . . . . (2)
We substitute the value of a = b - 2 from (2) in (1) to get,
(b - 2) -3b = 4
or, b - 2 - 3b = 4.
or, b -2 - 3b + 2 = 4 + 2 (adding 2 two both sides of the equation)
or, -2b = 6 (simplifying)
or, -2b/(-2) = 6/(-2) (dividing both sides by -2)
or, b = -3 (simplifying)
Now, we substitute this value of b = -3, in (2) to get
a = (-3) - 2
or, a = -5.
∴ (a, b) = (-5, -3)
Learn more about simultaneous equations at
#SPJ2